Comparative analysis of techniques for the limitation of compensation currents in multifunctional grid-tied inverters - Bonaldo, Jakson Paulo; Tofoli, Fernando Lessa; Arantes Monteiro, Raul Vitor; Morales-Paredes, Helmo Kelis [UNESP] (Elsevier B.V., 2021)
Multifunctional grid-tied inverters (MFGTIs) are capable of not only injecting the energy generated by renewable energy sources into the ac grid, but also performing other distinct tasks that include reactive power and harmonic compensation, as well as voltage support. For this purpose, reference currents must be generated to separate the current components associated with the energy injection and disturbance compensation. However, the inverter power capacity may not be high enough so that it is possible to perform both functions simultaneously. Thus, it is necessary to ensure that the primary objective regarding the injection of active power is accomplished, also limiting the capacity to mitigate power quality disturbances in terms of the maximum amplitude or rms value of the ac current. In this context, this work analyzes four control strategies for the limitation of currents in MFGTIs considering key aspects such as performance and power quality indices at the point of common coupling (PCC). Both simulation and experimental results are presented and thoroughly discussed so that it is possible to establish a fair comparison among the assessed approaches used to limit the power processed by the inverter according to the rated capacity and improve the grid power quality.
Keywords: Current compensation; Dynamic current saturation; Multifunctional grid-tied inverters; Power quality; Renewable energy sources